Photocatalytic degradation of 4-nitrophenol in aqueous TiO2 suspensions: Theoretical prediction of the intermediates - San, N; Hatipoglu, A; Koçtürk, G; Çinar, Z (ELSEVIER SCIENCE SA, 2002)
The kinetics of the photocatalytic degradation of 4-nitrophenol (4-NP) in the presence of TiO2 has been investigated experimentally and theoretically. The effects of the catalyst loading, the initial concentration of 4-NP, H2O2 and the added Cu2+ ions on the degradation rate have been examined. A pseudo-first order kinetic model has been used to describe the results. A linear dependence of the rate constant upon the reciprocal of the initial 4-NP concentration has been obtained. The addition of H2O2 increases the reaction rate while Cu2+ ions has a detrimental effect. With the intention of predicting the primary intermediates, geometry optimizations of the reactants, the products and the transition state complexes have been performed with the semi-empirical PM3 method. The molecular orbital calculations have been carried out by an SCF method using RHF or UHF formalisms. Based on the results of the quantum mechanical calculations, the rate constants of the two possible reaction paths have been calculated by means of the transition state theory, and 1,2-dihydroxy-4-nitro-cyclohexadienyl radical which then forms 4-nitrocatechol has been determined as the most probable primary intermediate by the application of three different theoretical shortcut methods. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: photocatalytic degradation; titanium dioxide; advanced oxidation; semiconductor photocatalysis; 4-nitrophenol; TITANIUM-DIOXIDE; PHOTODEGRADATION; PHENOL; OXIDATION; HYDROXYLATION; KINETICS; ACID; Chemistry